Estimating the Equity Value of PT Smartfren Telecom Tbk. Using Discounted Cash Flow and Relative Valuation (Journal of Business and Management, 2021)
The development of technology has changed the telecommunications industry, both globally and domestically, so that telecommunications companies have benefited as internet service providers where currently the internet has become a primary need for the community. PT Smartfren Telecom Tbk (FREN) is one of the leading telecommunications service providers in Indonesia which is part of the Sinar Mas group. As a telecommunications company, FREN should benefit from developments in the telecommunications industry, however, that development if telecommunication industry is not in line with the company's profit. Whereas FREN has an increasing trend in revenue from 2015 to 2020 with a CAGR of 21%. This study aims to analyze the intrinsic value of FREN’s equity and compare with the market price and industry multiples. The valuation method used in this study are discounted cash flow (DCF) with a free cash flow to firm model and relative valuation with EV/EBITDA. Based on the results of the calculation, the market price of FREN's shares is considered too high where the intrinsic value of FREN ranges from Rp51 to Rp78 which is lower than the closing price (July 16, 2021) which is Rp112Keywords: telecommunications, DCF valuation, intrinsic value, overvalued, relative valuation